Identification of Immunohistochemical Reagents for In Situ Protein Expression Analysis of Coronavirus-associated Changes in Human Tissues. Issue 1 (January 2021) - Szabolcs, Matthias; Sauter, Jennifer L.; Frosina, Denise; Geronimo, Jerica A.; Hernandez, Enmily; Selbs, Elena; Rapkiewicz, Amy V.; Rekhtman, Natasha; Baine, Marina K.; Jäger, Elke; Travis, William D.; Jungbluth, Achim A.
Abstract : We studied the suitability of commercially available monoclonal antibodies (mAbs) for the immunohistochemical (IHC) detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) in standard archival specimens. Antibodies were screened on HEK293 cells transfected with viral nucleoprotein, S1 subunit and S2 subunit of spike protein and on untransfected cells, as well as a panel of normal tissue. Lung tissue with presence of SARS-CoV2 confirmed by in situ hybridization (ISH) was also used. A total of 7 mAbs were tested: (1) mAb 001 (Sino Biological, 40143-R001), (2) mAb 007 (Sino Biological, 40150-R007), (3) mAb 019 (Sino Biological, 40143-R019), (4) mAb 1A9 (GeneTex, GTX632604), (5) mAb ABM19C9 (Abeomics, 10-10007), (6) FIPV3-70 (Santa Cruz, SC-65653), and (7) mAb 6F10 (BioVision, A2060). Only 2 mAbs, clone 001 to the nucleoprotein and clone 1A9 to the S2 subunit spike protein displayed specific immunoreactivity. Both clones showed strong staining in the acute phase of COVID-19 pneumonia, mostly in areas of acute diffuse alveolar damage, but were not completely congruent. Viral protein was also found in kidney tubules, endothelia of multiple organs and a nasal swab of a patient with persistent SARS-CoV2 infection. The other tested reagents were either poorly reactive or demonstrated nonspecific staining in tissues and lesions not infected by SARS-CoV2. Our study demonstrates that rigid specificity testing is mandatory for the evaluation of mAbs to SARS-CoV2 and that clones 001 to nucleoprotein and 1A9 to S2 subunit spike protein are useful for the in situ detection of SARS-CoV2.